The development of a universal design for learning-based storybook for student preparation to carry out implementation of national assessment - Rusilowati, Ani; Widiyatmoko, Arif; Abidin, Zaenal; Wulandari, Desi (AIP conference proceedings, 2023)
This research is focused on preparing students to deal with literacy and numeracy in minimum competency assessment (in Indonesia it is called AKM). This book is also designed to meet the demands of universal design for learning (UDL) so that it can be used by regular students and students with special needs. This study aims to: (1) develop UDL-based storybooks, (2) test the validity and readability of storybooks, (3) test the effectiveness of storybooks in instilling character, literacy and numeracy in science content students, and (4) test the practicality of using storybooks. The R & D research design begins with a theoretical exploration and review of the character, literacy and numeracy material that will be made in the story, validation of the developed storybook, testing the effectiveness of storybooks in instilling character and improving students’ literacy and numeracy and ending with a practical test of using storybooks. The test subjects were one grade students (Level I). The research instrument consisted of a validation sheet, a cloze test, a literacy test, a numeracy test, and a character scale. Data analysis techniques are descriptive and quantitative. Descriptive to measure the validity and readability of storybooks. Validity test using Aiken’s V, readability test using percentage. Quantitative, using effect size statistics, to measure changes in character, increase in literacy and numeracy before (baseline) and after reading storybooks (intervention). The results of the study are illustrated storybooks with the following characteristics: (1) presenting stories by presenting reading numeracy and literacy, (2) equipped with pictures or illustrations according to the stage of development of 1st-grade elementary school children, (3) equipped with AKM practice questions, (4) contains characters, (5) in accordance with the universal design of learning, so it is friendly for children with special needs. The practice questions adjust the AKM model, as a form of effort to prepare students to deal the AKM. The developed picture-storybook meets the valid criteria. Books are also effective for improving students’ literacy and numeracy, as well as familiarizing caring characters and enthusiasm for learning. Teachers, parents and students found the illustrated storybooks developed to be interesting and practical to use.